Perspectives on E-learning - Fanica Stroe (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
E-learning is one of the biggest challenges of the pandemic. To some extent, it means the perpetuation of today’s civilization. I have tried to rethink the e-learning stages of Professor Hubert Dreyfus by looking for new arguments and possible new solutions.